Improvement Lifeskill Training Ability in Household Electrical Systems in Politeknik Tanjungbalai - Muchsin Harahap; Marnida Yusfiani; Budi Handoko (Universitas Pendidikan Indonesia Kampus Purwakarta, 2021)
Tanjungbalai City is one of the cities located on the coast, with some of its people working as fishermen. Therefore, some ordinary people do not know the electricity system, both household and industrial electrical systems. This is deemed necessary to do an understanding of electricity. This understanding is intended to provide training in household electrical systems so that it is expected that they can carry out maintenance and repair independently and gain life skills to find work and create jobs. The training method is carried out in 3 steps, namely the delivery of basic electrical theory, demonstration exercises from drawing diagrams, making simulations assisted by the Electrical Control Techniques Simulator (EKTS) application, and testing the installation series starting from measurement, checking wire connections, troubleshooting the installation so that it is good and safe and evaluation through pre-training and post-training assessments. The data were analyzed by descriptive analyses and T-test SPSS 22. The result showed that participants’ understanding increased.